2020
DOI: 10.3389/fphys.2020.00600
|View full text |Cite
|
Sign up to set email alerts
|

FASN-Mediated Lipid Metabolism Regulates Goose Granulosa Cells Apoptosis and Steroidogenesis

Abstract: Lipid metabolism participates in regulating the functions of granulosa cells (GCs), which is important for follicular development. In this experiment, goose GCs from prehierarchical follicles and hierarchical follicles were selected to be the model for studying the putative regulatory role of lipid metabolism in apoptosis and steroidogenesis, through overexpression and interference with fatty acid synthase (FASN). When FASN was overexpressed, the lipid accumulation was increased in hierarchical GCs (hGCs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(44 reference statements)
2
6
0
Order By: Relevance
“…In the F1 follicle, the deposition of large amounts of yolk lipids was associated with cell proliferation and very-low-density lipoprotein transportation. Genes related to lipid metabolism were enriched at the ZT12 stage, which are essential for promoting the deposition of yolk protein and synthesis of lipids before the LH surge stage [ 46 ], For example, FASN is involved in lipid metabolism to regulate steroidogenesis in granulosa cells [ 47 ], and the observation that this gene was enriched in the ZT12 stage was consistent with the results of another study [ 48 ]. These findings suggested that cell proliferation and lipid metabolism in granulosa cells plays a pivotal role in follicle development before the LH surge stage [ 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…In the F1 follicle, the deposition of large amounts of yolk lipids was associated with cell proliferation and very-low-density lipoprotein transportation. Genes related to lipid metabolism were enriched at the ZT12 stage, which are essential for promoting the deposition of yolk protein and synthesis of lipids before the LH surge stage [ 46 ], For example, FASN is involved in lipid metabolism to regulate steroidogenesis in granulosa cells [ 47 ], and the observation that this gene was enriched in the ZT12 stage was consistent with the results of another study [ 48 ]. These findings suggested that cell proliferation and lipid metabolism in granulosa cells plays a pivotal role in follicle development before the LH surge stage [ 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…Increasing evidence has shown the importance of lipid metabolism in goose follicle development [ 30 , 31 ]; we also demonstrated that de novo lipogenesis occurs in goose GCs [ 17 ], revealing that the LD accumulation capacity of goose GCs depends on the different stages of follicle development, with the highest accumulation capacity during the preovulatory follicle stage [ 32 ]. The accumulation of LDs in the cytoplasm plays a key role in the energy balance, membrane synthesis, and cell signal transduction [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 59%
“…For the overexpression group, the expression levels of FASN increased to almost 78- and 330-fold compared to the control in phGCs and hGCs, respectively. For the interference group, the expression levels of FASN decreased to 0.42- and 0.37-fold compared to the control in phGCs and hGCs, respectively [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…GCs were isolated by 0.1% collagenase Ⅱ (Sigma, Aldrich, Burlington, MA, USA) digestion, then counted and cultured as previously described [ 26 ]. At 70~80% confluence, GCs were transfected with pEGFP-N1-FASN (2 μg/mL), pEGFP-N1 (2 μg/mL, control) and siRNA- FASN (90 pmol/mL), siRNA-NC (90 pmol/mL, control) individually using lipofectamine 3000 (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s instructions, and assayed at 48 h post-transfection [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation